Analysis of Posyandu Status and Health Service Ownership in the Sukoharjo District Health Office area: A Case Study of 2017-2021: Analisis Status Posyandu Dan Kepemilikan Layanan Kesehatan Diwilayah Dinas Kesehatan Kabupaten Sukoharjo: Studi Kasus Tahun 2017-2021 - Ismiyatun, I; Setiyadi, Noor Alis (Prosiding University Research Colloquium, 2023)
Posyandu is a Village Community Institution as a forum for community participation tasked with assisting in improving basic social services and the health sector. Health Service Facility is a tool and place to carry out health service efforts, both promotive, preventive, curative and rehabilitative carried out by the Government, local governments, and the community. Health facilities owned by the private sector are more than health care facilities owned by the government. There has not been much research exploring the status of posyandu and ownership of health services. This study aims to analyze the status of posyadu and describe the ownership of health services in the health office area. This research is a descriptive research by conducting a study of data obtained from posyandu data and health service ownership reported in the Sukoharjo Regency Health Office Profile from 2017-2021. The data of this study are secondary data. The data obtained is then analyzed descriptively using graphs. Result: Sukoharjo Regency has 12 sub-districts with 12 puskemas working areas. The number of posyandu status in the Sukoharjo Health Office area in 2017-2021 that has decreased is kartasura and gatak. The number of posyandu that fluctuates every year is in the Weru, Nguter and Bendosari areas. Areas that have increased the number of posyandu are tawangsari, sukoharjo, polokarto, mojolaban, grogol and baki. Ownership of health services is widely owned by the District Government and the private sector. The conclusion is that the number of posyandu that has increased is in the areas of Tawangsari, Sukoharjo, Polokarto, Mojolaban, Grogol and Baki. The number of posyandu that has decreased is in the Kartasura and Gatak areas. The fluctuating number of posyandu is among Weru, Nguter and Bendosari areas. Health service ownership in Sukoharjo Regency for five years from 2017-2021 the number of service ownership is more owned by the Regency Government and the Private Sector in 2017-2021.